Phytochemical and Antiplasmodial Evaluation of Five Colombian Plants with Ethnopharmacological Background of Antimalarial Use - Jorge Enrique Hernández-Carvajal; María Helena Arias-Marciales; José Octavio García; Yoshie Adriana Hata-Uribe; Giovanny Garavito-Cárdenas; Pilar Ester Luengas Caicedo (Tabriz University of Medical Sciences, 2023)
Background: The study of medicinal plants has made it possible to develop products and drugs for the treatment of different diseases. Several plants in Colombia have a history of popular use for the treatment of malaria. The objective of this work was to provide information on the antiplasmodic and phytochemical activity of five neotropical native plants with a folk use for the treatment of malaria. Methods: The ethanolic extract of each species was obtained by percolation method and characterized by thin-layer chromatography (TLC), high-performance liquid chromatography (HPLC), and hydrogen nuclear magnetic resonance (1H-NMR). The in vitro antiplasmodial activity was evaluated against Plasmodium falciparum (strain FCR-3, chloroquine-resistant). Results: Ethanolic extracts of Ambelania duckey, Cecropia metensis, Cecropia membranacea, and Verbena littoralis showed no activity. However, Curarea toxicofera extract exhibited an IC50 of 7.6 ± 3.9 μg/mL and was classified as moderately active. Most extracts show hemolytic concentration (CH50) > 1000 μg/ mL). A preliminary phytochemical study was carried out using tube analysis, TLC, HPLC, and 1H-NMR. Steroids or triterpenes, and phenolic compounds were detected by TLC in all extracts. These findings were confirmed by characteristic aliphatic and aromatic signals in 1H-NMR spectra, corresponding to triterpenes and phenolics, respectively. Additionally, alkaloids were extracted from C. toxicofera and detected by aromatic signals in 1H-NMR spectra. Conclusion: Ethanolic extract of C. toxicofera showed antiplasmodial activity (IC50 of 7.6 ± 3.9 μg/mL); this activity may be due to the bisbenzylisoquinoline alkaloids. The ethanol extracts of A. duckey, C. membranacea, C. metensis, and V. littoralis did not present antiplasmodial activity.